Design of Deterministic Model of Signal Transduction between Neuronal Cells - Hliatsevich, Maryna A.; Bulai, Pavel M.; Pitlik, Taras N.; Denisov, Andrey A.; Cherenkevich, Sergey N. (Mathematical Modelling and Analysis, 2015)
Mathematical model describing signal transduction between neurons has been presented using the system of nonlinear ordinary differential equations. The Cauchy problem for the given system has been solved numerically and system parameters were adjusted to match the results of experimental measurements of extracellular postsynaptic potentials in rat hippocampus slices. While fitting model to the experimental data some values of synaptic parameters have been determined.